THE STUDY OF SPEECH ACT ON MOVIE CITY OF EMBER - Nur Nikmah Putri Pamungkas (English Education Department Slamet Riyadi University Surakarta, 2019)
The aims in this study were (1) to describe the representative acts employed by the character’s in City of Ember movie. And (2) To describe the Locution, Illocution, and Perlocution of the representative acts uttered by the character’s City of Ember movie. The method of the study was descriptive qualitative method, by using this method researcher can classifying and analyzing the utterance on City of Ember movie. The data was collected through primary data and secondary data. In collecting data, the primary data was used from quota conversation in the script of City of Ember movie and the secondary data was used to complete and support the primary data were taken from books and articles. The result of this study shows that Representative was expressed in the form of informing, stating, refusing, concluding, and Agreeing. On this research representative only found five types they were stating (28, 5%), informing (28, 5%), refusing(23,8%), agreeing(9,5%), concluding(9,5%). Based on Searle’s category, researcher also find those utterance into Locutionary act, Illocutionary act, and the last Perlocutionary act. In this research the researcher hope that when studying about speech act, people can understand and decrease misunderstanding about speaker’s meaning. Key words: Speech act, City of Ember movie, Representative act, Descriptive qualitative method, Linguistic Study